HISTOLOGICAL RESPONSE OF PULP TO BELIMBING WULUH (Averrhoa bilimbi L.) GEL COMPARED TO CARBAMID PEROXIDE AS TOOTH WHITENING (IN VIVO) - Asih Rahaju; Henri Hartman; Ris Kristiana; Tiara Putri (Journal of Health and Dental Sciences, 2023)
A teeth whitening procedure is an action to get naturally bright teeth color. The teeth whitening process often has side effects on the tooth structure and its surroundings. Teeth whitening ingredients generally contain carbamide peroxide. One of the natural ingredients that can whiten teeth is Averrhoa bilimbi Linn. This study aimed to determine the effect of Averrhoa bilimbi L. gel and carbamide peroxide on the histological response of the pulp. The research method was carried out by processing Averrhoa bilimbi Linn into extracts through the maceration method and then making a gel with a concentration of 50%. The study was conducted on 27 rabbit incisors and divided into three groups (negative control group, 10% carbamide peroxide, and 50% Averrhoa bilimbi L. gel). Each group was exposed for 4 hours for 14 days, then the teeth were extracted, and the pulp was taken with K-file number 10-40 and continued to look at the histological picture. The data was processed using a one-way ANOVA statistical test; the statistical test results showed significant differences for the three groups with a p-value of 0.000 (p <0.05). It can be concluded that there is an effect of 50% Averrhoa bilimbi L. gel on the histological response of the pulp, there is an effect of 10% carbamide peroxide on the histological response of the pulp, and there is a significant difference between 10% carbamide peroxide and 50% Averrhoa bilimbi L. gel. DOI : 10.54052/jhds.v3n2.p125-134